Possibilities of Hyperinflammation Correction in COVID-19 - I. S. Simutis; G. A. Boyarinov; M. Yu. Yuriev; D. S. Petrovsky; A. L. Kovalenko; S. A. Parfenov (Антибиотики и Химиотерапия)
Objective. To evaluate the effect of sodium meglumine succinate on the severity of the systemic inflammatory response syndrome when used in complex therapy in patients with severe COVID-19.Material and Methods. The clinical and laboratory data of 12 patients with the diagnosis «Novel coronavirus infection COVID-19 complicated by community-acquired bilateral polysegmental interstitial pneumonia» were analyzed. All patients underwent intensive therapy with a limited volume of water load in the intensive care unit in accordance with the recommendations of the Ministry of Health of the Russian Federation. Seven patients (observation group) received a polyelectrolyte solution containing meglumine sodium succinate (Reamberin) as part of the therapy at a daily dose of 5 ml/kg during the entire period of stay in the ICU (3–10 days). The control group included 5 patients who received a similar volume of a conventional polyelectrolyte solution containing no metabolically active substrates. The study was pilot in nature due to the small number of patients. The laboratory parameters of arterial and venous blood were measured at the following stages: 1) upon admission to the ICU; 2) 2–4 hours after the completion of Reamberin infusion; 3) 8–12 hours after drug administration; 4) 24 hours after the start of intensive care. Mortality rate and the incidence of thrombotic complications in the groups were assessed on the 28th day of observation. The presence of the therapeutic intervention effect was established using multivariate analysis of variance (MANOVA).Results. A positive effect of the study drug on the severity of systemic inflammatory response syndrome (SIRS) against the background of ongoing etiotropic therapy was noted. Efficiency criteria were the correction of hyperfibrinogenemia, normalization of the platelet count, decrease in the level of C-reactive protein, ferritin, and leukocytosis. A significant decrease in the frequency of thromboembolic events was observed within 28 days of treatment, as well as a reduction in the length of time the patients spent in the ICU.Conclusion. Based on the results of the pilot study, it can be assumed that the antihypoxic and antiradical effects of the drug contribute to the reduction of pulmonary and systemic endotheliitis, which is characteristic of severe forms of the disease and, as a result, inhibits the development of the systemic inflammatory response syndrome. The data obtained can serve as a basis for further in-depth studies.